Working wetlands: classifying wetland potential for agriculture - McCartney, Matthew P.; Masiyandima, Mutsa; Houghton-Carr, H.A. (International Water Management Institute, 2005)
This paper reports on a form of multi-criteria analysis that provides a formal approach for evaluating the suitability of a wetland for specific agricultural uses, and ensures that explicit consideration is given to the possible consequences of such utilization. The method is based on a hybrid of ideas taken from concepts and methodologies related to: environmental flow assessments, land suitability classification and the hazard evaluation procedures used in the design of dams. The approach, which elaborates the idea of working wetlands, is generic, though the examples presented are for case studies from southern Africa.